Artistic representations of the sea and coast: implications for sustainability - Stocker, Laura; Kennedy, Deborah (International Centre of Landscape and Language, 2011)
This article explores artistic representations of Australian seas and coasts, and the power of art to sustain seas and coasts. Research into artworks at the National Gallery of Australia was supplemented with a study of other local public and private works. A number of substantive themes emerged in viewing the paintings;; the sea and coast has been represented as: sea country, sovereign territory, sublime spaces, a Romantic space of yearning, a psychological journey, a literal journey, a site of social and political comment, social places, ecological places and a site for industry. We discuss these themes, reflecting on the various expressions of human-sea relations and the cultural, political and ideological values that inform the artworks. This article points to possible artistic representations of sustainable seas and coasts. In turning to the power of art in sea and coastal sustainability, we discuss the potential of art to create shifts in consciousness and relationships by challenging humans to imagine the sea differently.